A sustainability framework for affordable housing in Malaysia - Phoo, Jing Yin (2020)
The rise of industrial revolution, Industrial Revolution 4.0 especially, urges the development technologically and scientifically which leads to the surge of higher living standard among the people. Paradoxically, people struggle to live the higher living standard life due to the surging house price. Despite of the situation, the supply and development of sustainable affordable housing remains low regardless of the national sustainable development goal. Several studies were conducted to discover the factors affecting the demand of affordable housing and the impacts of sustainable affordable housing. Nevertheless, there are limited studies to identify and prioritise the criteria of sustainable affordable housings in Malaysia from housing purchasers’ perspectives. Therefore, this study aims to identify the criteria for sustainable affordable housing and develop a sustainability framework for affordable housing purchasers in Malaysia. Literature review was carried out to determine the sustainable aspects by identifying the sustainable criteria for affordable housing. There are a total of twenty-seven (27) criteria identified and they are grouped under five (5) main sustainability groups which are, environmental, economic, social, cultural and technological. Quantitative method was conducted in this study, whereby questionnaires were designed and distributed to low-middle income earners to find out their agreement level on the importance of the twenty-seven criteria for sustainable affordable housing. In return, ninety-two (92) sets of questionnaires were collected from the respondents. The collected data were analyzed using Measure of Central Tendency to portray the ranking of each criteria. The results revealed that the economic aspect is the most important criteria to be considered for sustainable affordable housings. Mann-Whitney U Test was carried out to show the significant difference between the selection of ranking for criteria between male and female respondents; as well as between the respondents age less than 30 years old and over 30 years old. A preliminary motivation framework was proposed in this research. The proposed sustainability framework acts as a guideline for future potential affordable housing purchasers to consider the availability and importance of the sustainable criteria while considering to buying an affordable housing. The findings could be disseminated to the Malaysian Government, professional bodies and property developers in order to deliver more sustainable affordable housings in the future.